CLINICAL AND EPIDEMIOLOGICAL ANALYSIS OF SNAKEBITE VICTIMS TREATED AT THE TROPICAL DISEASES HOSPITAL BETWEEN 2020-2023 - Guedes, Ana Beatriz Gonçalves de Sousa; Cardoso, Jean Matheus Guedes; Arruda, Rejanne Lima (Seven Editora, 2025)
Snakebite accidents represent a major public health problem in Brazil, especially in tropical regions such as Tocantins, where there is a high incidence of these events. This study aimed to describe the clinical and epidemiological profile of snakebite victims treated at the Hospital de Doenças Tropicais (HDT), in Araguaína-TO, between 2020 and 2023. This is a retrospective, quantitative, descriptive study, based on the analysis of 457 medical records. The data revealed a predominance of male patients (77.68%), young patients, especially between 20 and 29 years old, and residents of rural areas. Most accidents occurred in the rainy months, with the main etiological agent being the genus Bothrops (78%), followed by Crotalus (20%). The cases were mostly classified as moderate (47.7%). The time between the accident and care varied, with only 5.25% being treated within one hour. The most affected areas were the lower limbs (90.59%). Most hospitalizations lasted between 2 and 7 days, and interventions such as drainage and debridement were performed in cases with local complications. The use of antibiotics was identified in 22.1% of cases, with emphasis on the combination of ciprofloxacin and clindamycin. The results reinforce the importance of early care and preventive actions aimed at the most vulnerable populations, in addition to supporting professional training strategies and public policy planning.DOI: https://doi.org/10.56238/sevened2025.028-004